Anchoring Transition Induced by Gelation in a Liquid Crystal System. Issue 2 (18th December 2012) - Bhargavi, R.; Nair, Geetha G.; Prasad, S. Krishna
Abstract We report a novel type of anchoring transition (ANT) in a liquid crystal driven by the physical gelation of the system. The ANT manifests as anomaly in the thermal behaviour of the dielectric permittivity. Data from X‐ray studies suggest that ANT is caused by the ability of the gel fibres to compete with the substrate‐driven orientation conditions. It is further found that the molecular reorientation is possible only in cases where the gel is weak, the difference between weak and strong gels being established by rheological measurements.